EVALUATION OF SELECTED SOYBEANS GENOTYPES AT TWO LOCATIONS - & et al., Mahmoud (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
In order to evaluate soybeans genotypes in two locations, five selected in sixth generation of selection were used with nursery in Baghdad, using RCBD with three replication. The results raveled superiority of selected promising genotypes in growth duration, flowers, plant height and number of branches, and yield component, as a number of plant bodes, 100 seed weight and number of seeds in bodes, especially genotype C, which produced seeds yield  (2758 kg h-1). Genotypes D was the best in oil content (23.05%), while  B genotype was highest in protein content (43.9%) compare with local variety, which gave lower values for all growth traits, when grown in different environments. It could be conclude that the hybridization impacted improving the traits of growth,  yield, protein and oil percent and selection of the genotype, as well as the superiority of genotypes promising when grown in different environments. So, can be conclude planting genotypes in several seasons and locations, under the influence of  package integrated technologies prior to their adoption factors.